The Relationship Between Length of Illness and Psycho-Social Problems of Cancer Responden Undergoing Chemotherapy - Sugiyanto, Emilia Puspitasari; Mulyono, Mulyono; Lazuardi, Nugroho (Journal of Language and Health, 2024)
Cancer is one type of disease with a poor prognosis, the stigma of a deadly disease is one of the factors that causes responden diagnosed with cancer to experience psychological changes. In the initial diagnosis, most will cause a psychosocial response in cancer responden, one of which is a psychological response. Cancer responden undergoing chemotherapy experience various psychosocial disorders including depression, anxiety, and stress. This study aims to determine the relationship between the duration of illness and the incidence of depression, anxiety, and stress in cancer responden This study used a quantitative correlational cross-sectional approach to 5responden. Data were analyzed using person product moment. The results of the study showed that there was a relationship between the length of illness and the incidence of depression, anxiety, and stress in cancer responden.ConclusionsIn further research, it is hoped that other factors such as complications and the effects of chemotherapy on the incidence of psychosocial problems in cancer responden can be analyzed.